The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1515/znc-1999-9-1005
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Chloride Salt Stress Induced Changes in Thylakoid Pigment-Protein Complexes, Photosystem II Activity and Thermoluminescence Glow Peaks

Abstract: Salt stress, Thylakoid membrane, Pigment-protein complex, PS II, Thermoluminescence, Mung bean ( Vigna radiata L.), Indian mustard (Brassica juncea Coss.)In the present study, mung bean (Vigna radiata L.) -a salt susceptible and Indian mustard (.Brassica juncea L.) -a salt resistant crop was studied to find out the differences in stress responses of these crops. Seedlings were grown in water soaked cotton under continuous illumination of 35 (.imole m 2 s 1 at 26 ± 1 °C. Salinity treatment of 0, 0.5 and 1.0% (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 7 publications
1
23
0
1
Order By: Relevance
“…Thermoluminescence glow curves are extensively used to decipher the changes in charge recombination in photosystem II (18,19,21). The TL bands at 10°C and 32°C are widely studied and well characterized (2-6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermoluminescence glow curves are extensively used to decipher the changes in charge recombination in photosystem II (18,19,21). The TL bands at 10°C and 32°C are widely studied and well characterized (2-6).…”
Section: Discussionmentioning
confidence: 99%
“…These samples were excited by a sequence of two flashes (General Radio, Stroboslave) with a halfdecay time of 3 ms (0.5 J) white light and quickly frozen to 77K by dropping them into a Dewar containing liquid nitrogen. TL glow curves were recorded as described by Misra et al (18,19). To inhibit electron transfer between Q A and Q B in the reaction centre of photosystem II, 5 mL 10 mmol/L DCMU was added to the chloroplast thylakoid sample before illumination.…”
Section: Measurement Of Thermoluminescencementioning
confidence: 99%
“…In some studies salt stress had no effect on PS2 (Robinson et al 1983, Brugnoli and Björkman 1992, Morales et al 1992. The PS2 inhibition under salt stress was characterized by Misra et al (1999). In some reports, the PS2 activity was decreased in response to salt stress due to the dissociation of 23 kDa polypeptide extrinsically bound to PS2 (Kuwabara and Murata 1982, Miyao and Murata 1983, Murata et al 1992.…”
Section: Salt Stress Effects On Photosynthesismentioning
confidence: 99%
“…In the red alga Porphyra perforata, Satoh et al (1983) demonstrated that the salinity stress-induced decrease in PSII activity was due to a decrease in the excitation energy reaching PSII reaction centers, as well as damage to the oxidizing side of PSII. Salt stress also inhibits PSII activity in higher plants (Everard et al 1994;Tiwari et al 1997;Misra et al 1999), including salt-tolerant plants such as mangroves (Parida et al 2003). In some reports, the eVects of salt stress on PSII were due to the dissociation of the 23-kDa polypeptide extrinsically bound to PSII (Murata et al 1992).…”
Section: Introductionmentioning
confidence: 99%